Genetic Approach to Thrombophilia - Bertina, Rogier M. (Thrombosis and Haemostasis, 2001)
Venous thrombosis is a multifactorial disease. Multiple interactions between genetic and environmental factors contribute to the development of the disease. Presently, we know of six or seven genetic risk factors for venous thrombosis. However, together these defects can explain the clustering of thrombotic events in only a small subset of families with thrombophilia. As to the identification of new genetic risk factors for thrombosis, we seem to have arrived at the end of a practicable road with the classical approach of thrombophilia, which usually starts with the study of the association of hemostatic phenotypes and thrombotic risk. At the same time we have undertaken various genetic approaches aiming at identifying polymorphisms/ mutations causing thrombotic risk. This review summarizes what we have learnt so far, what to do and what not to do. The odds for finding remaining common genetic risk factors for venous thrombosis during the next ten years may be predicted to be fairly high.
Keywords: Thrombophilia; venous thrombosis; genetic risk factors; polymorphisms